2017
DOI: 10.1016/j.ecss.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term scenarios of mercury budgeting and exports for a Mediterranean hot spot (Marano-Grado Lagoon, Adriatic Sea)

Abstract: The Marano-Grado Lagoon (MGL) is extensively contaminated by mercury (Hg) from local sources and long-term (500 years) tidally delivered inputs from the Idrija Hg mine (Slovenia) through Isonzo River suspended loads. A multibox WASP-7 (Water Analysis Simulation Program) model was used to simulate the long-term dynamics of the mercury cycle in the MGL. Scenario simulations were used to compute changes in the system over 100 years. Present and future Hg concentrations in water, sediment, and Hg budgets were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The WASP7 Hg model/MERC7 submodel (Wool et al, 2001) is a dynamic process-based model designed to simulate the Hg cycle within a system of well-mixed discrete spatial units (layers) of water and sediment as well as the exchanges of the system with its boundaries. This model has been already adapted and successfully applied to a shallow environment in a 2D configuration (Canu & Rosati, 2017;Melaku Canu et al, 2015), and is here used in a 1D configuration to explore Hg dynamics along an extended redox gradient. Figure 3 shows the conceptual model of the processes that affect the evolution of the state variables (Table S2).…”
Section: Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The WASP7 Hg model/MERC7 submodel (Wool et al, 2001) is a dynamic process-based model designed to simulate the Hg cycle within a system of well-mixed discrete spatial units (layers) of water and sediment as well as the exchanges of the system with its boundaries. This model has been already adapted and successfully applied to a shallow environment in a 2D configuration (Canu & Rosati, 2017;Melaku Canu et al, 2015), and is here used in a 1D configuration to explore Hg dynamics along an extended redox gradient. Figure 3 shows the conceptual model of the processes that affect the evolution of the state variables (Table S2).…”
Section: Model Structurementioning
confidence: 99%
“…Global Biogeochemical Cycles 10.1002/2017GB005700 WASP7 Hg model /MERC7 sub-model (Wool et al, 2001) and already succefully applied in shallow waters (Canu & Rosati 2017;Melaku Canu et al, 2015). One-dimensional (1-D) modeling has widely been used to investigate the biogeochemical and ecological features of the basin (Grégoire & Soetaert, 2010;Konovalov et al, 2004;Lamborg et al, 2008;Oguz et al, 2000;Yakushev et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contribution of organic matter and nutrient deposition to estuarine sediment via urban run-off during the monsoon season, resulted in a two-fold and five-fold increase in methanogenesis and denitrification respectively, increasing the production of the greenhouse gases nitrous oxide (N2O) and methane (CH4). Canu and Rosati (2016) modelled the long-term (100 yrs) dynamics of the mercury cycle in the Marano-Grado Lagoon (a Mediterranean mercury hotspot), and showed that a sea level rise (of 0.315 m) and temperature rise (+2.5°C) may increase sediment methylmercury (MeHg) by up to 87% and 95% of current levels. Mercury bioaccumulation in biota was projected to increase accordingly.…”
Section: Pollution and Contaminationmentioning
confidence: 99%
“…The investigation of the biogeochemical dynamics of Hg species in the marine environment addresses the need to accurately model sources and pathways of this priority contaminant within and among the different abiotic and biotic compartments of the aquatic ecosystem (Driscoll et al, 2013;Batrakova et al, 2014). Over the last few years some theo-retical studies have offered innovative tools to reproduce the mass balance and the dynamics of [Hg] in the marine environment by means of biogeochemical models based on interconnected zero-dimensional boxes representing water or sediment compartments: among these are the River MERLIN-Expo model (Ciffroy, 2015) and the WASP (Water Analysis Simulation Program) model (Melaku Canu et al, 2015;Canu and Rosati, 2017;Rosati et al, 2018). In particular, the River MERLIN-Expo model (Ciffroy, 2015) has been used to reproduce the spatiotemporal distribution of inorganic and organic contaminants in the 1D domain of rivers and to calculate the mass balance for each of them.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years some theo-retical studies have offered innovative tools to reproduce the mass balance and the dynamics of [Hg] in the marine environment by means of biogeochemical models based on interconnected zero-dimensional boxes representing water or sediment compartments: among these are the River MERLIN-Expo model (Ciffroy, 2015) and the WASP (Water Analysis Simulation Program) model (Melaku Canu et al, 2015;Canu and Rosati, 2017;Rosati et al, 2018). In particular, the River MERLIN-Expo model (Ciffroy, 2015) has been used to reproduce the spatiotemporal distribution of inorganic and organic contaminants in the 1D domain of rivers and to calculate the mass balance for each of them. Although the model is able to describe many of the physical and chemical processes involved in fresh water and sediment, it specifically targets environments characterized by (i) nearly homogeneous water bodies and (ii) limited variations in landscape geometry.…”
Section: Introductionmentioning
confidence: 99%